Efektifitas Penyerapan Tenaga Kerja Skill Pada Program “Pemagangan Dan Worplace Training” Pemerintah Aceh - Mahmud Mahmud; Azwar Yunus; Zulfadli Zulfadli; Aswar Aswar; Hilmi Hilmi; Muhammad Dirhamsyah (Akademi Komunitas Negeri Aceh Barat, 2022)
AbstractBased on data released by the Central Statistics Agency for Aceh Province in 2021, it stated that Aceh Province was the poorest province on the island of Sumatra, one of the triggers was the high open unemployment rate which reached 6.30% in mid-February 2021, one of the methods used to solve the problem. Problems with this high unemployment rate, the Aceh Government took the initiative in 2019 to start an acceleration program for the process of absorbing skill workers through domestic apprenticeship programs and workplace training placed by partner companies with the Aceh Province Manpower and Population Mobility Office for 3-5 months. The purpose of this study is to trace the effectiveness of labor absorption through this program, which has been carried out by the Aceh government from 2019 to 2021. The results of this study indicate that the percentage of skilled workforce recruitment after the implementation of domestic apprenticeship programs and workplace training is 68%. in 2020 and 78% in 2021. This percentage can be categorized as an effective program. Keywords:Apprenticeship; Labor; Aceh Government; Skills;__________________________ AbstrakBerdasarkan data yang dirilis oleh Badan Pusat Statistik Provinsi Aceh pada tahun 2021 menyebutkan Provinsi Aceh menjadi provinsi termiskin di Pulau Sumatera, salah satu pemicunya adalah tingginya angka tingkat pengangguran terbuka yang mencapai 6,30% pada medio februari 2021, salah satu metode yang digunakan untuk menyelesaikan permasalahan tingginya angka penggangguran ini, Pemerintah Aceh berinisiatif pada tahun 2019 mulai membuat program akselerasi untuk proses penyerapan tenaga kerja skill melalui program pemagangan dalam negeri dan workplace training yang ditempatkan perusahaan mitra kerjasama Dinas Tenaga Kerja Dan Mobilitas Penduduk Provinsi Aceh selama 3-5 bulan. Penelitian ini bertujuan untuk mengetahui efektifitas penyerapan tenaga kerja melalui program ini, yang sudah dilakukan oleh pemerintah Aceh dari tahun 2019 sampai dengan 2021. Hasil dari kajian ini menunjukkan besaran persentase perekrutan tenaga kerja skill setelah pelaksanaan program pemagangan dalam negeri dan workplace training sebesar 68% pada tahun 2020 dan 78% pada tahun 2021. Besaran persentase ini dapat dikategorikan program berjalan secara efektif. Kata Kunci:Pemagangan; Tenaga Kerja; Pemerintah Aceh; Skill; Workplace Training.